Asuntos teóricos y metodológicos de la cultura organizacional (2009)
This paper is concerned with Organizational Culture (OC), its components and the main techniques to study it. It states that measuring and establishing its impacts related with results, efficiency, healthy and welfare of employees are important issues for any manager —public or private. But measure culture is not enough, we need to be engage with both manage and shape it according to the organizational context.